Effects of low Reynolds number on flow stability of a transonic compressor. (March 2015) - Zhao, Shengfeng; Lu, Xingen; Zhu, Junqiang; Ge, Han; Chengwu, Yang
As the aircraft cruising at high altitude over 20, 000 m with subsonic speed, the Reynolds number in terms of the compressor blade becomes very low and the compressor performance decreases dramatically due to separation of boundary layer and secondary-flow. The main objective in this paper is to understand the physical mechanism by which Reynolds number affects the compressor stable range. In this paper, a series of steady and unsteady numerical simulations were carried out for a transonic compressor rotor under several conditions, which corresponded to the operations at sea level, and at high altitude. Detailed analyses of the flow visualization have exposed the different flow topologies of the complicated secondary flow. It was found that the transonic axial-flow compressor rotor used in current investigation was prone to tip stall behavior, and the complex flow mechanisms which occur near the blade tip are found to be the key factors for the limited flow stability both under high Reynolds number and low Reynolds number. Under high Reynolds number, the tip flow field was dominated by the low momentum zones generated by the interaction between tip leakage flow and incoming flow, and with the decrease of Reynolds number, the tip leakage flow was weakened and the low-momentum fluid due to the surface boundary layer separation and radial transport of low-energy fluid was dominant in the tip flow.